Does radioiodine therapy in patients with differentiated thyroid cancer increase the frequency of another malignant neoplasm? - Hirosawa, Renata Midori [UNESP]; Marivo, Monica; Luengo, Juliana de Moura Leite; Tagliarini, Jose Vicente; Castilho, Emanuel Cellice; Marques, Mariangela de Alencar; Kiy, Yoshio; Marone, Marilia Martins Silveira; Silveira, Liciana Vaz de Arruda; Mazeto, Glaucia Maria Ferreira da Silva (Isrn Oncology, 2011)
Objectives. To compare the frequency of another primary malignancy in patients with differentiated thyroid carcinoma (DTC) who received radioiodine therapy or not ((131)I). Material and Methods. 168 cases of DTC patients were retrospectively evaluated as to the frequency of another neoplasia by comparing patients with and without it, taking into account clinical, laboratory, and therapeutic parameters. Results. Another primary malignancy occurred in 8.9% of patients. Of these, 53.3% showed the malignancy before (131)I and 46.7% after it. By comparing both groups, the age at the moment of diagnosis of another neoplasia was 46.1 ± 20.2 years for the group before (131)I therapy and of 69.4 ± 11.4 years for the group after it (P = 0.02). Of the 148 patients treated with (131)I, 4.7% developed another malignancy. The latter were older (61 ± 17 years) than those who did not show another cancer type (44.1 ± 14.2 years) (P < 0.05). Conclusion. The frequency of another neoplasia found after (131)I was similar to that found before (131)I.